Bilateral phyllodes tumor: Case report - Isabel Mayorga-Pérez; Patricia Mulero-Soto; Kerwin Cruz-De La Rosa; Viviana Negrón-González; Jonathan Hernandez-Rosa; Jose Feneque-Gonzalez; Maria Correa-Rivas; Anwar Abdul-Hadi (Elsevier, 2024)
Introduction: Phyllodes tumors are rare fibroepithelial neoplasms showing a prominent intracanalicular architectural pattern with leaf-like stromal fronds lined by epithelial and myoepithelial cell layers, and accompanied by stromal hypercellularity that may be confused with cellular fibroadenomas. They represent less than 0.5-1% of all primary breast tumors and their presentation is even rarer in children. Clinically, diagnosis can be suggested by large size, rapid growth and occurrence in older patients. Surgery is the treatment of choice, but it may vary from an excisional biopsy to a total mastectomy. We present a 15 year-old female with Autism-Spectrum Disorder, biopsy concerning of fibroadenoma and final pathology remarkable for bilateral phyllodes tumor. Case report: A 15-year-old female with history of Autism Spectrum Disorder (ASD) was seen due to bilateral breast masses. A couple of days later, patient presented to the Emergency Room with ulceration and bleeding from the left breast mass and patient was schedule for an urgent mastectomy. The pathology disclosed a multifocal, aggressive type phyllodes tumor with moderate stromal cellularity, moderate stromal atypia, high mitotic index, corresponding to a Borderline phyllodes tumor. Based on the history of a rapid enlarging ulcerated mass, and the presence of a mass in her right breast, she was scheduled for resection of the right breast. Conclusion: We present one of the few cases in the literature of a pediatric patient who presents with an aggressive type of bilateral phyllodes tumor. Our case report enlightens the importance of clinical suspicion of these tumors to offer the best treatment.